(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Any resource or location on the Internet has a unique IP address associated with it. DNS is like a phone book. We remember the phone numbers, or have the numbers on speed dial or saved on our cells etc. of those people who we call frequently. Similarly, in computers (having Windows OS), a HOSTS file works as a speed dial for the computer and directs the computer to the number to be called. But at certain times we need to call someone that is not listed in the speed dial or memory. At such times DNS is very helpful. DNS consists of a vast database of name of servers and their corresponding IP addresses. For example, on typing www.google.com inThe Web browser, the host sends that address to a DNS server. The DNS server then searches for information matching to ’google.com’ in its internal database. On matching, it then retrieves the corresponding IP address and sends it back to the computer. The computer then knows where to find the Internet resources